2014
DOI: 10.15287/afr.2014.178
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Norway spruce [Picea abies (L.) Karst.] in Romanian Carpathians

Abstract: Abstract. The genetic diversity of Romanian most important coniferous tree species, the Norway spruce, was estimated by means of allozyme markers. A total of 695 adult trees sampled from eleven populations grouped in six mountainous areas in the Romanian Carpathians were analyzed. In three metapopulations (Maramureş, Postăvar and Parâng), to evaluate the influence of altitudinal gradient on genetic diversity, samples were collected from populations located at high and low altitude. At other location (Apuseni M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Whereas, no consistent relationship of altitude and diversity between studies are reported. Comparing stands of Norway spruce growing in low elevations with high altitude stands, higher diversity was reported for the high-altitude [36,121] or intermediated populations [37], but also no correlation has been described [32], which is, correspondingly, our observation for neighboring stands of different origin.…”
Section: Genetic Variation and Differentiationcontrasting
confidence: 58%
“…Whereas, no consistent relationship of altitude and diversity between studies are reported. Comparing stands of Norway spruce growing in low elevations with high altitude stands, higher diversity was reported for the high-altitude [36,121] or intermediated populations [37], but also no correlation has been described [32], which is, correspondingly, our observation for neighboring stands of different origin.…”
Section: Genetic Variation and Differentiationcontrasting
confidence: 58%
“…However, other Carpathian and local seedlots showed poor performance (Figure 3), confirming previously noticed possible variation within one region as wide as between distant origins [14] due to high genetic variation [12]. Good adaptation of transferred provenances might depend on sufficient genetic diversity, which, for the Norway spruce populations in the Carpathian Mountains in Ukraine and Romania, were reported to be moderate to high, with no significant differences regarding altitude [51,52]. Similar to our results, both the most productive transferred Central European seedlots and the best performing local provenances were reported to show similar growth in long-term trials in Southeast Norway [53].…”
Section: Provenance Effect On Growth Performancesupporting
confidence: 84%
“…A low level of overall genetic differentiation found between three out of the five of the studied populations (supported by F st , UPGMA, and Structure analysis) may result from combined effect of different factors, such as outcrossing rate, reproductive system, and high rate of pollen-mediated gene flow in this species [45]. Namely, due to low average pollen grain weight and low sedimentation velocity [48], pollen from coniferous tree species can travel tens or hundreds of kilometers, providing gene flow across a wide distribution area [50].…”
Section: Discussionmentioning
confidence: 77%
“…Nuclear microsatellites have been extensively employed in studying genetic variation of coniferous tree species [12,[43][44][45][46]. In the present study, genetic variation within and between populations and their genetic structure were analyzed in five natural populations of Norway spruce from Serbia, using eight EST-SSR markers.…”
Section: Discussionmentioning
confidence: 99%